2023
DOI: 10.1111/prd.12542
|View full text |Cite
|
Sign up to set email alerts
|

Biological biomarkers of oral cancer

Allan Radaic,
Pachiyappan Kamarajan,
Alex Cho
et al.

Abstract: The oral squamous cell carcinoma (OSCC) 5 year survival rate of 41% has marginally improved in the last few years, with less than a 1% improvement per year from 2005 to 2017, with higher survival rates when detected at early stages. Based on histopathological grading of oral dysplasia, it is estimated that severe dysplasia has a malignant transformation rate of 7%–50%. Despite these numbers, oral dysplasia grading does not reliably predict its clinical behavior. Thus, more accurate markers predicting oral dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 240 publications
0
5
0
Order By: Relevance
“…Considering the anti-cancer, anti-metastatic, and chemopreventive effects of natural polyphenols on oral cancer, several researchers investigated the mechanisms of action of these agents [29]. Kapoor et al [30] found that [6]-gingerol (1) can significantly inhibit the proliferation of oral cancer cells (OCCs) by inducing apoptosis and G2/M phase arrest. 6-Gingerol can also inhibit OCC migration and invasion by regulating N-cadherin and vimentin, inducing AMPK activation in Ca9-22 cells, and inhibiting the AKT/mTOR signalling pathway.…”
Section: Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the anti-cancer, anti-metastatic, and chemopreventive effects of natural polyphenols on oral cancer, several researchers investigated the mechanisms of action of these agents [29]. Kapoor et al [30] found that [6]-gingerol (1) can significantly inhibit the proliferation of oral cancer cells (OCCs) by inducing apoptosis and G2/M phase arrest. 6-Gingerol can also inhibit OCC migration and invasion by regulating N-cadherin and vimentin, inducing AMPK activation in Ca9-22 cells, and inhibiting the AKT/mTOR signalling pathway.…”
Section: Polyphenolsmentioning
confidence: 99%
“…The antibiotic antimycin A (52) mediates the apoptosis of OCC CAL27 and Ca9-22 cells by increasing oxidative stress and ROS production [86]. Nitrated [6,6,6] tricycle (53)-derived compounds induce apoptosis and DNA damage in OCC by inducing oxidative stress [87]. Meanwhile, pseudolaric acid B (54) significantly inhibits the caspase-dependent apoptosis of HN22 cells [88].…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allan Radaic etc. made an exhaustive summary of potential oral microbiome-based biomarkers for OSCC [82]. It is possible to distinguish cancerous lesions from normal tissues and perform tumor staging by noninvasively detecting microbes [83].…”
Section: Diagnosis and Gradingmentioning
confidence: 99%
“…Early diagnosis of OSCC is challenging due to its insidious onset, resulting in a significant proportion of patients being diagnosed at advanced stages ( 5 ). Despite advancements in diagnostic and treatment approaches over the past few decades, the five-year overall survival rate remains below 50 percent ( 6 ). Timely diagnosis of OSCC enables surgical resection and improves patient survival rates ( 7 ).…”
Section: Introductionmentioning
confidence: 99%